Beyond expectations: disease duration and psychological burden in psoriatic arthritis. - YURDAKUL, OZAN VOLKAN; Kılıç G.; KÜÇÜKAKKAŞ, OKAN; Kılıç E.; KESKİN, YAŞAR; Tekeoğlu İ.; Sargın B.; Cengiz G.; Balta N. C.; Alkan H.; Kasman S. A.; Şahin N.; et al. (My University, 2023)
This study aims to investigate the relationship between disease duration and psychological burden in PsA and to identify the risk factors associated with psychological distress. Patients with PsA who met CASPAR classifcation criteria enrolled by Turkish League Against Rheumatism (TLAR)-Network. Patients were categorized into three groups based on disease duration: early stage (<5 years), middle stage (≥5,<10 years), and late stage (≥10 years). All patients underwent clinical and laboratory assessment using standardized protocol and case report forms. The associations between psychological variables and clinical parameters were assessed by a multivariate analysis. Of the 1113 patients with PsA (63.9% female), 564 (%50.7) had high risk for depression and 263 (%23.6) for anxiety. The risk of psychological burden was similar across all PsA groups, and patients with a higher risk of depression and anxiety also experienced greater disease activity, poorer quality of life, and physical disability. Multivariate logistic regression revealed that female gender (OR=1.52), PsAQoL (OR=1.13), HAQ (OR=1.99), FiRST score (OR=1.14), unemployment/retired (OR=1.48) and PASI head score (OR=1.41) were factors that infuenced the risk of depression, whereas the current or past enthesitis (OR=1.45), PsAQoL (OR=1.19), and FiRST score (OR=1.26) were factors that infuenced the risk of anxiety. PsA patients can experience a comparable level of psychological burden throughout the course of their disease. Several socio-demographic and disease-related factors may contribute to mental disorders in PsA. In the present era of personalized treatment for PsA, evaluating psychiatric distress can guide tailored interventions that improve overall well-being and reduce disease burden.
Keywords: Anxiety; Arthritis; Psoriatic; Depression; Rheumatic diseases; Quality of life